ANALISIS PENANAMAN SIKAP PEDULI LINGKUNGAN MELALUI PEMBELAJARAN IPAS PADA SISWA KELAS V DI SDN 04 SINGKAWANG - Angga Prayoga; Wahyuni Oktavia; Safrihady (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: (1) Environmental Care Attitude of grade V students at SDN 04 Singkawang (2) factors that influence the cultivation of environmental care attitudes through IPAS learning in grade V students of SDN 04 Singkawang. This research is a qualitative research, with questionnaire, interview and documentation methods. The subjects in this study were 34 people which included 1 educator from 33 students from class V SDN 04 Singkawang. The reason the researcher made class V as an informant is because they are at a stage of cognitive, social, and moral development that allows them to understand, respond, and express attitudes towards environmental issues quite well. In addition, they have obtained relevant learning materials, so they are considered appropriate and strategic in exploring the environmental care attitudes of elementary school students. The results showed that (1) Environmental Care Attitude of grade V students at SDN 04 Singkawang showed a level of concern for the environment. Their behavior shows five main indicators, namely, hard work, initiative, respect for cleanliness, responsibility, and wise use of resources. To build a strong and consistent attitude of environmental care, strengthening through habituation, continuous education, and the active role of parents and teachers are still needed; (2) factors that influence the cultivation of environmental care attitudes through IPAS learning in grade V students of SDN 04 Singkawang are 2, namely, supporting factors and inhibiting factors. In the supporting factors there is the role of the teacher, Active and Contextual Learning Methods, Adequate Facilities and Infrastructure, Parental Involvement, and Habituation and Routine Activities. While the inhibiting factors are the lack of individual student awareness, the surrounding environment, limited facilities, and limited IPAS learning time / hours.